NECK TRAUMA BY BICYCLE HANDLEBAR IN ROAD TRAFFIC ACCIDENT – A RARE CASE REPORT WITH REVIEW OF LITERATURE (Journal of Forensic Medicine & Toxicology, 2012)
A 22 year old man died on the spot in a road accident  due to laceration injury over his neck. He was brushed by a  passing car from behind while traveling on a bicycle. The  deceased lost the control his bicycle and fell over the exposed  metallic right end of the rotating handlebar of bicycle. He  sustained a horizontally placed laceration injury over the  front and both sides of the middle third of neck. Though the  pediatric blunt abdominal trauma secondary to bicycle  handlebar is widely reported but a fatal neck injury in an adult of this nature is certainly extraordinary and deserves mentioning in the forensic literature.
Keywords: Neck Laceration; Bicycle Handlebar; Road Accident; Carotid artery; Jugular vein; Trachea